2000
DOI: 10.15760/etd.661
|View full text |Cite
|
Sign up to set email alerts
|

Joint Angle Tracking with Inertial Sensors

Abstract: The need to characterize normal and pathological human movement has consistently driven researchers to develop new tracking devices and to improve movement analysis systems. Movement has traditionally been captured by either optical, magnetic, mechanical, structured light, or acoustic systems. All of these systems have inherent limitations. Optical systems are costly, require fixed cameras in a controlled environment, and suffer from problems of occlusion. Similarly, acoustic and structured light systems suffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 22 publications
2
10
0
Order By: Relevance
“…IMUs are used in aerospace, marine and automotive fields and are now increasingly used for human motion tracking in several clinical applications. [29][30][31][32][33][34][35][36][37][38][39][40][41][42][43] We used IMUs from Xsens Technologies (XSens MTx, www.xsens.com). Under controlled conditions of motion using a Gimbal table, the Xsens MTx IMUs have demonstrated an absolute mean precision of 0.3° to 1.0° depending on the axis of rotation under slow conditions of motion when compared to an optical motion tracking system (Optotrak).…”
Section: Main Outcome: Measures Of Cervical Spine Motion (Figure 2)mentioning
confidence: 99%
“…IMUs are used in aerospace, marine and automotive fields and are now increasingly used for human motion tracking in several clinical applications. [29][30][31][32][33][34][35][36][37][38][39][40][41][42][43] We used IMUs from Xsens Technologies (XSens MTx, www.xsens.com). Under controlled conditions of motion using a Gimbal table, the Xsens MTx IMUs have demonstrated an absolute mean precision of 0.3° to 1.0° depending on the axis of rotation under slow conditions of motion when compared to an optical motion tracking system (Optotrak).…”
Section: Main Outcome: Measures Of Cervical Spine Motion (Figure 2)mentioning
confidence: 99%
“…Numerous industrial operations yield liquid effluents which are normally contaminated with toxic or poisonous substances. The textile industry plays a vital role in the global economy as well as in our daily life, but at the same time, it consumes large amount of water and generates huge quantities of wastewaters [1]. The main chemical contaminants present in textile wastewater are synthetic dyes, heavy metals, biocides, pentachlorophenol, free formaldehyde, halogen carriers, softeners and fire retardants [2].…”
Section: Introductionmentioning
confidence: 99%
“…Ref. [1] demonstrated that wearable inertial sensors can be used to develop metrics for objective measurements of tremor and dyskinesia in individuals suffering from Parkinson's disease, whereas the authors of [12] developed an inertial ambulatory monitoring system that provides a complete motor assessment of tremor, bradykinesia, and hypokinesia. Ref [13] presented a novel interactive method for recognizing handwritten words using inertial sensors included into smartwatches.…”
Section: Related Workmentioning
confidence: 99%
“…Constant tracking motions and position of aging or convalescent people in their natural living environment helps understand the cause of many diseases and thus provides valuable information for medical diagnosis and/or feedback on the treatment efficacy. Among the common neurological problems that affect human motor functions are Parkinson disease, multiple sclerosis, stroke, traumatic brain injury, and spinal cord injuries [1]. If a patient is supposed to perform exercises on their own, a human motion capture system can replace surveillance from medical personnel.…”
Section: Introductionmentioning
confidence: 99%